1981
DOI: 10.1159/000207102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Spleen on the Blood Distribution of the Colony-Forming Cells (CFU-C) in Man

Abstract: The incidence of the blood committed granulocyte progenitor cells (CFU-C) before and after epinephrine administration has been studied in 10 normal, 16 splenomegalic and 8 splenectomized subjects through a double-layer agar culture system. A significant increase of the mean values of CFU-C per milliliter of blood has been observed after epinephrine administration in normal and in splenomegalic subjects. In splenectomized patients the baseline mean values of CFU-C per milliliter of blood were higher than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In cirrhotic patients the con centration of blood CFU-GM was slightly reduced, but the difference to normal sub jects was not statistically significant. A slight decrease of blood CFU-GM, due to increased margination within the spleen, had been previously reported; CFU-GM could be removed from the spleen to blood with epinephrine [6]. The nonsigni ficant decrease of blood CFU-GM alone cannot explain the greatly decreased gran ulocytic growth we found in liquid cul tures of cells from cirrhotic patients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In cirrhotic patients the con centration of blood CFU-GM was slightly reduced, but the difference to normal sub jects was not statistically significant. A slight decrease of blood CFU-GM, due to increased margination within the spleen, had been previously reported; CFU-GM could be removed from the spleen to blood with epinephrine [6]. The nonsigni ficant decrease of blood CFU-GM alone cannot explain the greatly decreased gran ulocytic growth we found in liquid cul tures of cells from cirrhotic patients.…”
Section: Discussionsupporting
confidence: 63%
“…It may be the expression of a more generally increased turnover of the monocyte-mac rophagic system in these patients that re quires further investigation. Our data seem to indicate that both granulocyte trapping within the spleen, associated or not with distruction [1,6], and reduced granulocyte production may be present in cirrhotic patients. The latter does not ap pear to be due to decreased concentration of CFU-GM, but possibly to increased committment of CFU-GM towards the monocyte-macrophagic line or to mecha nisms operating directly on the proliferat ing granulocytic pool.…”
Section: Discussionmentioning
confidence: 76%
“…Golde reported inhibition of murine in vitro colony-forming cells (CFU-C)' by dexamethasone (3) and Zalman et al (4) confirmed this finding, demonstrating an 18% decrease in the number of CFU-C when 6 X 1o-8 M dexamethasone was incorporated into the culture. Finally, in a study of the effect of hydrocortisone on human CFU-C, Morra et al (5) found that 1 mg of hydrocortisone added to in vitro cultures decreased the growth of CFU-C by -24% (5). Using the Luxol Fast Blue stain, it has been shown that 50% of the circulating CFU-C (6) and 10-40% of the bone marrow CFU-C are eosinophilic, with the remainder being neutrophil/macrophage precursors (7,8).…”
Section: Introductionmentioning
confidence: 99%